The Influence Of Work Discipline And Work Performance On Employee Performance Through Organizational Culture As An Intervening Variable In The Work Unit Of The Pamekasan Regency Transportation Office - Teguh Isgunanto; Sutoyo; Lintang Suminar; A'isy Fiklik Nafisah; Yosa Endriatmoko (PT Maju Malaqbi Makkarana, 2025)
Human resources or employees are the key to determining the success of an organization, so that every employee is not only required to have knowledge, skills, and abilities, but also must have experience, motivation, self-discipline, and high work spirit. So that if employee performance is good, the organization's performance will increase, leading to the achievement of desired goals and objectives. The success of an organization is judged by the success of the organization in achieving goals and objectives as well as the achievement of vision and mission. The first reason is because both the direct and indirect influence of Employee Performance shows a significant influence. Both indirect coefficients of influence have a value smaller than the direct path coefficient (0.233<0.767). This states that the higher the work discipline and work achievement, the more employee performance increases with the increase in organizational culture.